2014
DOI: 10.4103/2277-9175.137870
|View full text |Cite
|
Sign up to set email alerts
|

Is there a place for open intramedullary nailing in femoral shaft fractures?

Abstract: Background:Femoral shaft fractures are among the most common fractures following high trauma injuries. Different kinds of treatment have been suggested for these injuries.Aim:The aim of this study was to compare the results femoral fractures treated by mini open and close intramedullary nailing (IMN) technique.Materials and Methods:A total of 48 adult patients were operated due to fracture of the femur with close or open IMN technique between September 2010 and September 2011. 23 patients operated with close. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Many authors have described a number of techniques for achieving closed reduction of femur fractures but these techniques still require some forms of intra-operative imaging or fracture table, and extra skin incisions [19][20][21]. However, mini-open reduction as we did for some of the fractures has been reported by previous studies with outcome comparable to that of closed reduction [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have described a number of techniques for achieving closed reduction of femur fractures but these techniques still require some forms of intra-operative imaging or fracture table, and extra skin incisions [19][20][21]. However, mini-open reduction as we did for some of the fractures has been reported by previous studies with outcome comparable to that of closed reduction [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Further supporting the notion of trochanteric entry nails, another study on cadavers found lesser structural and iatrogenic injury to the surrounding structures and the gluteal musculature with trochanteric nailing [ 38 ]. In our series, open reduction was performed in about one-third of patients and this approach was secondary to difficult closed reduction procedure, which has consistently been described as a safe alternative technique [ 39 , 40 ]. In this study, external fixation for the treatment of femoral shaft was primarily performed for open fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also suggested the ease of learning the technique of entry through greater trochanteric tip that resulted in improved functional outcomes; although there is no differece in the rates of union among the two entry sites. Another prospective cohort study on antegrade femoral nailing reported similar higher rate of union, lower complication rates, and comparable functional results of trochanteric insertion as compared to the piriformis fossa nailing [34]. In addition, the authors demonstrated lesser uoroscopy and operation time with greater trochanter entry in obese patients.…”
Section: Discussionmentioning
confidence: 82%